A coupled recursive least squares algorithm for multivariable systems and its computational amount analysis by using the coupling identification concept - Jin, Yu; Ding, Feng (International journal of adaptive control and signal processing, 2024)
Summary In order to solve the problem of the parameter identification for large‐scale multivariable systems, which leads to a large amount of computation for identification algorithms, two recursive least squares algorithms are derived according to the characteristics of the multivariable systems. To further reduce the amount of computation and cut down the redundant estimation, we propose a coupled recursive least squares algorithm based on the coupling identification concept. By coupling the same parameter estimates between sub‐identification algorithms, the redundant estimation of the subsystem parameter vectors are avoided. Compared with the recursive least squares algorithms, the proposed algorithm in this article have higher computational efficiency and smaller estimation errors. Finally, the simulation example tests the effectiveness of the algorithm.